Willingness to pay for improved solid waste management and associated factors among households in Debre Berhan town, North Shoa Zone, Amhara, Ethiopia, 2022 - Chernet, Dawit; Sema, Wondimu; Gebeyehu, Amare; Wogayehu, Belachew Tekleyohannes (Frontiers in Sustainability, 2024)
Background The willingness to pay for better solid waste management serves as a framework that allows households to contribute a maximum amount of money to service improvement. Objectives This study determined the willingness to pay for improved solid waste management and the associated factors among households in Debre Berhan town, Ethiopia, in 2022. Methods A community-based cross-sectional study was conducted in Debre Berhan town, from June to July 2022. Multistage sampling techniques were employed to select household heads using semi-structured and pre-tested questionnaires. Data were entered using EpiData version 4.6 and analyzed using Stata version 14. The multivariable Tobit regression model was built upon a univariable Tobit regression framework. The relationship between dependent and independent variables was declared statistically significant in the final model at a p-value of ≤0.05 in the 95% confidence interval. Results This study included 518 households, with a response rate of 99.23%. A total of 472 households 91.1% (95% CI: 88.1–93.5) reported their willingness to pay for improved solid waste management. The average monthly willingness to pay was 54.83 Ethiopian Birr. The amount of solid waste generated (β: 10.49; 95% CI: 2.85–18.12), knowledge (β: 7.33; 95% CI: 2.43–12.22), perception (β: 10.01; (95% CI: 5.83–14.19), monthly income (β: 13.23; 95% CI: 6.20–20.26), education level (β: 14.30; 95% CI: 3.48–13.63), house ownership (β: 8.56; 95% CI: 3.48–13.63), family size (β: 3.88; 95% CI: 2.01–5.74), and being a female household head (β: 5.73; 95% CI: 1.73–9.70) were the significantly associated factors. Conclusion Willingness to pay for improved solid waste management services was high. The town municipality should take advantage of this willingness to pay by installing an improved solid waste management, which can help alleviate budget constraints through active household participation in funding these services.